2002
DOI: 10.1291/hypres.25.939
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antihypertensive Agents on the Survival Rate of Polycystic Kideney Disease in Han: SPRD Rats.

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disorder in humans. Hypertension is one of the major complications, and its control might affect the renal survival and disease mortality. Suitable antihypertensive agents have been discussed based on clinical and animal studies, but no definitive conclusion has been reached. Generally, therefore, all antihypertensives are indiscriminately treated as if providing the same level of blood pressure control. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Using tail-cuff plethysmography, mild hypertension was detected in Pkd1 +/− mice aged 30 weeks. Increased SBP measured by the same method has been reported in 20-week-old Han/SPRD rats [14]. The hands-off measurement of blood pressure using telemetry revealed that, in stressfree animals, blood pressure was similar in Pkd1 +/+ and Pkd1 +/− mice.…”
Section: Discussionsupporting
confidence: 72%
“…Using tail-cuff plethysmography, mild hypertension was detected in Pkd1 +/− mice aged 30 weeks. Increased SBP measured by the same method has been reported in 20-week-old Han/SPRD rats [14]. The hands-off measurement of blood pressure using telemetry revealed that, in stressfree animals, blood pressure was similar in Pkd1 +/+ and Pkd1 +/− mice.…”
Section: Discussionsupporting
confidence: 72%
“…Until now, several drugs have proven effective in Han:SPRD rats, but most of these studies were short-term observations, among which only two studies reported a survival time [16,28]. The present study demonstrates that rosiglitazone had short-term therapeutic effects in Han:SPRD rats in multiple experiments.…”
Section: Discussionsupporting
confidence: 47%
“…High blood pressure is the most important risk factor in patients with ADPKD; clinically, uncontrolled hypertension leads to a deterioration of renal function in ADPKD patients [10]. Higashikuni et al [11] reported that even in individuals without hypertension, the risk of albuminuria decreased in parallel with decreasing blood pressure in chronic kidney disease (CKD) patients.…”
Section: Introductionmentioning
confidence: 99%